2020
DOI: 10.3390/biomedicines8120599
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Oncogenic Targets by the Tumor-Suppressive miR-139 Duplex (miR-139-5p and miR-139-3p) in Renal Cell Carcinoma

Abstract: We previously found that both the guide and passenger strands of the miR-139 duplex (miR-139-5p and miR-139-3p, respectively) were downregulated in cancer tissues. Analysis of TCGA datasets revealed that low expression of miR-139-5p (p < 0.0001) and miR-139-3p (p < 0.0001) was closely associated with 5-year survival rates of patients with renal cell carcinoma (RCC). Ectopic expression assays showed that miR-139-5p and miR-139-3p acted as tumor-suppressive miRNAs in RCC cells. Here, 19 and 22 genes were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Our previous studies revealed that miR-139-3p (the passenger strand of pre- miR-139 ) acts as a tumor-suppressive miRNA in bladder cancer [ 33 ] and renal cell carcinoma [ 34 ]. A single miRNA can control a vast number of RNAs in cells, and the genes controlled by a miRNA vary from cell to cell.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that miR-139-3p (the passenger strand of pre- miR-139 ) acts as a tumor-suppressive miRNA in bladder cancer [ 33 ] and renal cell carcinoma [ 34 ]. A single miRNA can control a vast number of RNAs in cells, and the genes controlled by a miRNA vary from cell to cell.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is also correlated with longer OS. miR-139-3p and its guide strand miR-139-5p are involved in ccRCC pathogenesis and expression levels of both miRNA and several of their target genes are correlated with clinical outcomes [ 108 ]. A tumor suppressor role has also been described in bladder cancer [ 109 ], CRC [ 110 ], glioblastoma multiforme [ 111 ], BC [ 45 ], and HCC [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from cell lines and subjected to this study as described previously [ 42 , 57 , 58 ]. The TaqMan probes and primers used in this study are listed in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…Transfection of siRNAs and miRNAs into OSCC cell lines was performed using Lipofectamine RNAiMAX reagent (Invitrogen, Carlsbad, CA, USA) according to our previous studies [ 42 , 57 , 58 ]. The reagents used in this study are listed in Table S4 .…”
Section: Methodsmentioning
confidence: 99%